FINANCIAL MANAGEMENT OF IT INNOVATIONS IN FOREIGN ECONOMIC MARKETING PROJECTS OF INVESTOR ENTERPRISES - Галич, Олександр; Федірець, Олег; Литвинов, Євгеній; Чопик, Олександр; Мироненко, Вадим; Квіта, Галина (Fìnansovo-kreditna dìâlʹnìstʹ: problemi teorìì̈ ta praktiki (Online), 2025)
The article examines the current aspects of financial management of IT innovations in the context of foreign economic activity of agro-processing investor enterprises of the western region of Ukraine. The study is based on a comprehensive analysis of financial, investment, and marketing indicators of four leading enterprises that actively integrate digital technologies into their activities and enter international markets. The authors substantiate the feasibility and effectiveness of using the latest financial controlling tools, taking into account the level of internationalization, innovation development indices, and economic dynamics of each enterprise. Special attention is paid to building a complex model for assessing the financial management of IT innovations, which allows for a systematic measurement of the integral effect of digital transformations on the financial and economic stability, export capacity, and strategic competitiveness of companies. The analysis of the results revealed both the strengths of the implementation of IT innovations in foreign economic activity and potential vectors of further growth, in particular in the aspects of analytics, digital integration, and strategic marketing management. The results of the study confirm that the digitalization of financial management can significantly enhance the effectiveness of international projects, contributing to the economic adaptability and innovative sustainability of enterprises in the context of global competition.